2017
DOI: 10.1038/leu.2017.8
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical targeting of aggressive T-cell malignancies using anti-CD5 chimeric antigen receptor

Abstract: The outlook for T-cell malignancies remain poor due to the lack of effective therapeutic options. Chimeric antigen receptor (CAR) immunotherapy has recently shown promise in clinical trials for B-cell malignancies, however, designing CARs for T-cell based disease remain a challenge due to the shared surface antigen pool between normal and malignant T-cells. Normal T-cells express CD5 but NK (natural killer) cells do not, positioning NK cells as attractive cytotoxicity cells for CD5CAR design. Additionally, CD5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(111 citation statements)
references
References 31 publications
3
107
0
Order By: Relevance
“…Approaches directed against this antigen face the same difficulties as CD7-directed approaches since CD5 is also a pan T-cell marker. Two studies showed that NK-92 expressing CD5-directed CARs were efficient in vitro against CD5-positive cell lines and primary tumour cells, and developed anti-tumour activity in vivo [33, 34]. Additionally, the use of anti-CD3 CAR-equipped NK-92 against primary peripheral T-cell lymphoma cells and T-cell leukaemia cell lines was investigated showing cytotoxic activity in vitro and against Jurkat cells in a xenogeneic mouse model [35].…”
Section: Car-modified Nk Cells Against Leukaemia and Lymphomamentioning
confidence: 99%
“…Approaches directed against this antigen face the same difficulties as CD7-directed approaches since CD5 is also a pan T-cell marker. Two studies showed that NK-92 expressing CD5-directed CARs were efficient in vitro against CD5-positive cell lines and primary tumour cells, and developed anti-tumour activity in vivo [33, 34]. Additionally, the use of anti-CD3 CAR-equipped NK-92 against primary peripheral T-cell lymphoma cells and T-cell leukaemia cell lines was investigated showing cytotoxic activity in vitro and against Jurkat cells in a xenogeneic mouse model [35].…”
Section: Car-modified Nk Cells Against Leukaemia and Lymphomamentioning
confidence: 99%
“…As a consequence, the FDA recently approved two commercial CAR-T cell therapies for relapsed/refractory B-ALL and relapsed/ refractory diffuse large B-cell lymphoma (DLBCL) (tisagenlecleucel) [101 & ,102] and for the second-line treatment of DLBCL (axicabtagene ciloleucel) [103 & ,104]. Their development is now being expanded and explored through other malignancies targeting CD5 [105] and CD7 [106] in T cell malignancies, FLT3, CD33, CD38, CD56, CD117, CD123, NKG2DL and Lewis-Y in AML [107], CD30 in Hodgkin lymphoma [108] or B-cell maturation antigen (BCMA) (breakthrough therapy designation by the FDA), CD19, CD38, CD138, TACI and SLAMF7 in multiple myeloma patients [109,110].…”
Section: Chimeric Antigen Receptor T Cell Therapymentioning
confidence: 99%
“…This shared antigenicity can cause fratricide in CAR T cells, inhibiting their proliferation and viability, and leading to normal T cells depletion and deep impairment of host immunity. To avoid this drawback, an anti-CD5 CAR transduced into a human Natural Killer (NK) cell line was tested (59). This approach showed potent anti-tumor activity against a variety of T-cell leukemia and lymphoma cell lines as well as primary tumor cells, and was able to demonstrate significant inhibition of disease progression in xenograft mouse models of T-cell ALL.…”
Section: T-cell Targets For Non-b-cell Lymphoproliferative Disordersmentioning
confidence: 99%